2009
DOI: 10.1590/s0100-204x2009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de métodos de análise de adaptabilidade e estabilidade fenotípica em feijoeiro-comum

Abstract: O objetivo deste trabalho foi comparar métodos de estudo de adaptabilidade e estabilidade fenotípica de feijoeiro-comum (Phaseolus vulgaris). Foram utilizadas avaliações de produtividade em 71 ensaios, com 16 genótipos em cada um. A adaptabilidade e a estabilidade dos genótipos foi avaliada por meio de seis métodos, e a associação entre os métodos foi determinada pela correlação de Spearman. Os métodos de Cruz e de Eberhart & Russel apresentaram forte correlação entre si. Os métodos de Lin & Binns, Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 9 publications
4
35
0
21
Order By: Relevance
“…In agreement with Arias et al (1996) the use of models with more than three components, from the biological point of view, is unsatisfactory, besides being difficult to handle, in relation to the possible benefits. The first three axes together explained 67.2% of the variation (PC1 = 32.6%; PC2 = 23.0% and PC3 = 11.6%), similarly to values found by Carbonell et al (2004), Melo et al (2007) and Pereira et al (2009), in common beans. Furthermore, with the significance level of 5%, we selected the AMMI3 model (Table 2).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…In agreement with Arias et al (1996) the use of models with more than three components, from the biological point of view, is unsatisfactory, besides being difficult to handle, in relation to the possible benefits. The first three axes together explained 67.2% of the variation (PC1 = 32.6%; PC2 = 23.0% and PC3 = 11.6%), similarly to values found by Carbonell et al (2004), Melo et al (2007) and Pereira et al (2009), in common beans. Furthermore, with the significance level of 5%, we selected the AMMI3 model (Table 2).…”
Section: Resultssupporting
confidence: 70%
“…Some studies have suggested adjustments to the AMMI method like the inclusion of additional genotype (AG), to increase the precision of identifying superior lines (Pacheco et al, 2005). Pereira et al (2009) suggested obtaining an index that considers the average of the absolute scores of each line in each significant component, weighted by the percentage of explanation of each significant component (AWAS), to facilitate the interpretation of results and identification of lines with high stability. Based on the AWAS index, the AWASY index wasproposed, which uses the weighted average of the absolute scores associated with the weighting of average yield of lines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several methods were used simultaneously to evaluate genotypes and production environments of different crops (Silva and Duarte 2006, Cargnelluti Filho et al 2007, Melo et al 2007, Silva Filho et al 2008, Pereira et al 2009, Guerra et al 2010, Nunes et al 2011, Gouvêa et al 2011). However, the AMMI has seldom been used together with the GGE Biplot in studies on sugarcane.…”
Section: Introductionmentioning
confidence: 99%